2020
DOI: 10.1097/j.pain.0000000000002102
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory and psychological phenotypes associated with neuropathic pain in entrapment neuropathy

Abstract: Supplemental Digital Content is Available in the Text. The severity more than the presence of neuropathic pain is related to the extent of neuropathy and a compromise of emotional well-being in entrapment neuropathies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(59 citation statements)
references
References 59 publications
(31 reference statements)
5
53
0
Order By: Relevance
“…We should note though that whereas psychological parameters were more pronounced in patients with CTS compared to healthy volunteers in our study, average scores were not considered clinically relevant. These findings are in line with previous reports in patients with CTS [42].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…We should note though that whereas psychological parameters were more pronounced in patients with CTS compared to healthy volunteers in our study, average scores were not considered clinically relevant. These findings are in line with previous reports in patients with CTS [42].…”
Section: Discussionsupporting
confidence: 94%
“…We recruited patients from surgery waiting lists, which is likely to include more severe profiles. However, symptom and function severity in our study was comparable with previous CTS cohorts from primary care [60] and secondary care [42]. The examiner who performed psychophysical testing could not be blinded to group allocation (CTS vs. healthy).…”
Section: Limitationssupporting
confidence: 76%
See 1 more Smart Citation
“…Median nerve conduction studies in CTS cases evaluate both sensory and motor nerve fibers. Electrophysiological severity classification in CTS is a useful method to show these evaluation parameters on a single scale [ 11 , 12 ], and there are many reports on clinical evaluations using severity classifications [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. However, as shown in this paper, the existing severity classifications do not always accurately reflect the severity of disease, and our results suggest the need to reevaluate previous studies that used these classifications.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have dedicated significant effort to determining the characteristics of NeuP in patients with carpal tunnel syndrome. Matesanz et al reported that the severity of NeuP is associated with more pronounced deficits in emotional well-being and sleep quality ( 3 ). Oteo-Alvaro and Marin revealed that numbness/tingling, pain intensity, and neurologic affectation are risk factors for NeuP ( 4 ).…”
Section: Introductionmentioning
confidence: 99%